Caring for the carers: Ensuring the provision of quality maternity care during a global pandemic. Issue 3 (May 2021) - Wilson, Alyce N.; Ravaldi, Claudia; Scoullar, Michelle J.L.; Vogel, Joshua P.; Szabo, Rebecca A.; Fisher, Jane R.W.; Homer, Caroline S.E.
Abstract: The COVID-19 pandemic is impacting health systems worldwide. Maternity care providers must continue their core business in caring and supporting women, newborns and their families whilst also adapting to a rapidly changing health system environment. This article provides an overview of important considerations for supporting the emotional, mental and physical health needs of maternity care providers in the context of the unprecedented crisis that COVID-19 presents. Cooperation, planning ahead and adequate availability of PPE is critical. Thinking about the needs of maternity providers to prevent stress and burnout is essential. Emotional and psychological support needs to be available throughout the response. Prioritising food, rest and exercise are important. Healthcare workers are every country's most valuable resource and maternity providers need to be supported to provide the best quality care they can to women and newborns in exceptionally trying circumstances.